Blurred Authenticity in Social Media Marketing: A Literature Review on Its Impact on Consumer Trust - Mukhamad Rinda Rifa’i (Finance : International Journal of Management Finance, 2026)
Background: The proliferation of social media platforms has created an environment in which branded content and genuine personal expression increasingly coexist within the same communicative space, generating conditions of systematic authenticity ambiguity that threaten consumer trust formation. Objective: This study introduces and theorizes blurred authenticity as a structural condition of social media marketing and examines the mechanisms through which it affects consumer trust, with the aim of advancing an integrated conceptual framework applicable to influencer marketing practice. Method: A conceptual narrative literature review synthesizing five anchor studies was complemented by an exploratory qualitative inquiry involving seventeen purposively selected informants from University of Cahaya Surya, encompassing students, lecturers, content creators, and public relations practitioners. Data were analyzed using thematic analysis following Braun and Clarke's six-phase framework. Results: Findings identify narrative-niche consistency as the dominant authenticity heuristic among consumers, cited by 82.4% of informants. Three trust maintenance mechanisms were empirically validated: perceived transparency, narrative coherence, and value alignment. Transparent commercial disclosure enhances trust only when accompanied by substantively candid content. Perceived value misalignment between creators and endorsed brands generates durable trust erosion extending beyond the immediate interaction. Conclusion: Blurred authenticity is a systemic rather than individual phenomenon requiring structural responses from brands, creators, and platforms. Brands that prioritize narrative fit in influencer selection and support genuine communicative candor in branded content are best positioned to sustain consumer trust in increasingly saturated digital markets. Future research should pursue longitudinal, experimental, and cross-cultural designs to validate and extend the conceptual model advanced here.